CHRAC1 promotes human lung cancer growth through regulating YAP transcriptional activity. (27th October 2021) - Wang, Mingwei; Li, Shasha; Guo, Wencong; Wang, Lulu; Huang, Jiaxin; Zhuo, Junzhe; Lai, Botao; Liao, Chenqi; Ge, Tianlan; Nie, Yuxuan; Jin, Su; Wang, Manxiang; et al.
Abstract: ATP-dependent chromatin remodeling complexes regulate chromatin structure and play important roles in gene expression, differentiation, development and cancer progression. Dysregulation in the subunits of the complexes often has been found in different cancers, but how they influence cancer initiation and progression is not fully understood. Here, we show that Chromatin Accessibility Complex Subunit 1 (CHRAC1), the accessory subunit of chromatin remodeling complex, is highly expressed in lung cancer tissues, which correlates with poor prognosis in lung cancer patients. CHRAC1 overexpression promotes lung cancer cell proliferation and migration in vitro and tumor growth in genetically engineered Kras G12D.LSL lung adenocarcinoma mouse model. Consistent with this, CHRAC1 silencing inhibits cell proliferation and migration in lung cancer cells and suppresses tumor growth in xenograft mouse model. Further, CHRAC1 binds to the transcription coactivator Yes-associated protein (YAP), enhances the transcription of downstream target oncogenes in Hippo pathway and thus promotes the tumor growth. Together, our study defines a critical role of CHRAC1 in promoting YAP transcriptional activity and lung cancer tumorigenesis, which makes it a potential target for lung cancer. Abstract : CHRAC1 promotes human lung cancer growth by enhancing the transcriptional activity of YAP and high expression of CHRAC1 was associated with poor survival of patients with lung cancer. Graphical Abstract: